Stress in the social context: a behavioural and eco-evolutionary perspective - MacLeod Kirsty J.; English Sinead; Ruuskanen Suvi K.; Taborsky Barbara (Company of Biologists Ltd, 2025)
The social environment is one of the primary sources of challenging stimuli that can induce a stress response in animals. It comprises both short-term and stable interactions among conspecifics (including unrelated individuals, mates, potential mates and kin). Social stress is of unique interest in the field of stress research because (1) the social domain is arguably the most complex and fluctuating component of an animal's environment; (2) stress is socially transmissible; and (3) stress can be buffered by social partners. Thus, social interactions can be both the cause and cure of stress. Here, we review the history of social stress research, and discuss social stressors and their effects on organisms across early life and adulthood. We also consider cross-generational effects. We discuss the physiological mechanisms underpinning social stressors and stress responses, as well as the potential adaptive value of responses to social stressors. Finally, we identify outstanding challenges in social stress research, and propose a framework for addressing these in future work.